Stable water isotope data 2021-2023 from Lobor village (near Zlatar town) - Maja Briški; Mirja Pavić; Staša Borović; Marco Pola (PANGAEA, 2023)
Measured values of δ18O and δ2H, associated d-excess values, and amount of collected precipitation from Lobor village, near Zlatar town
In: Briški, M et al. (2023): Stable water isotope data (δ18O and δ2H) of monthly precipitation from 2021 to 2023 (NW Croatia) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.961245